Dietary changes during pregnancy and the postpartum period in Singaporean Chinese, Malay and Indian women: the GUSTO birth cohort study. Issue 9 (28th June 2013) - Chen, Ling-Wei; Low, Yen Ling; Fok, Doris; Han, Wee Meng; Chong, Yap Seng; Gluckman, Peter; Godfrey, Keith; Kwek, Kenneth; Saw, Seang-Mei; Soh, Shu E; Tan, Kok Hian; Chong, Mary Foong Fong; et al.
Abstract Objective To examine changes in food consumption during pregnancy and the postpartum period in women of major Asian ethnic groups. Design Using interviewer-administered questionnaires, we assessed changes in food consumption during pregnancy (26–28 weeks' gestation) and the postpartum period (3 weeks after delivery) as compared with the usual pre-pregnancy diet. Setting Singapore. Subjects Pregnant women (n 1027) of Chinese, Malay and Indian ethnicity (mean age 30·4 (sd 5·2) years) who participated in the Growing Up in Singapore Towards healthy Outcomes (GUSTO) study. Results During pregnancy, participants tended to increase their consumption of milk, fruit and vegetables and decrease their consumption of tea, coffee, soft drinks and seafood (all P < 0·001). Most participants reported adherence to traditional restrictions ('confinement') during the early postpartum period (Chinese: 94·8 %, Malay: 91·6 %, Indian: 79·6 %). During the postpartum period, participants tended to increase their consumption of fish and milk-based drinks and decrease their consumption of noodles, seafood, and chocolates and sweets (all P < 0·001). Ethnic differences in food consumption were pronounced during the postpartum period. For example, most Chinese participants (87·2 %) increased their ginger consumption during the postpartum period as compared with smaller percentages of Malays (31·8 %) and Indians (40·8 %; P for ethnic difference <0·001). Similar ethnic differences were observed for cooking wine/alcohol, herbs and spices, and herbal tea consumption. Conclusions Marked changes in food consumption that reflect both modern dietary recommendations and the persistence of traditional beliefs were observed in Singaporean women during pregnancy and the postpartum period. Traditional beliefs should be considered in interventions to improve dietary intakes during these periods.